1988
DOI: 10.2337/diab.37.6.723
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Glycemic Potentiation: Sensitive Indicator of β-Cell Loss in Partially Pancreatectomized Dogs

Abstract: To determine which test of islet function is the most sensitive indicator of subclinical beta-cell loss, we studied six conscious dogs before and 1 and 6 wk after removal of the splenic and uncinate lobes [64 +/- 2% pancreatectomy (PX)]. To assess hyperglycemic potentiation, acute insulin secretory responses (AIR) to 5 g i.v. arginine were measured at the fasting plasma glucose (FPG) level after PG was clamped at approximately 250 mg/dl and after PG was clamped at a maximally potentiating level of 550-650 mg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
5

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 15 publications
5
34
5
Order By: Relevance
“…Moreover, we have assessed in vivo measures ofbeta cell reserve in donors using the technique ofglucose potentiation of arginine-induced insulin secretion. Our observations in humans confirms the experimental evidence in animals (3,11) that partial pancreatectomy leads to a decrease in the functional reserve of the beta cell.…”
Section: Resultssupporting
confidence: 80%
“…Moreover, we have assessed in vivo measures ofbeta cell reserve in donors using the technique ofglucose potentiation of arginine-induced insulin secretion. Our observations in humans confirms the experimental evidence in animals (3,11) that partial pancreatectomy leads to a decrease in the functional reserve of the beta cell.…”
Section: Resultssupporting
confidence: 80%
“…This finding suggests that simple β-cell mass reduction is insufficient to produce β-cell dysfunction or that a greater degree of mass reduction is necessary. The ability of the reduced number of β-cells in this in vitro model to adapt functionally is in keeping with observations of β-cell functional adaptation to decreased mass in rodents [24] and dogs [25].…”
Section: Discussionsupporting
confidence: 58%
“…However, no information is available concerning pulsatile insulin release in these patients. A 64% pancreatectomy in dogs also led to a decrease in insulin secretion in response to arginine that was most pronounced at increased plasma glucose concentrations (i.e., glucose potentiation was decreased) (30). In humans after hemipancreatectomy and dogs after an approximately two-thirds pancreatectomy, both the fasting plasma glucose and the insulin concentrations (measured by conventional immunoassay) were normal, raising the question, "How does a decreased capacity for insulin secretion adapt to prevent the development of diabetes?"…”
Section: Discussionmentioning
confidence: 99%
“…This approach is to be contrasted to measuring insulin clearance by infusing exogenous insulin, which has been shown to be unaffected by a partial pancreatectomy (30). We previously showed that partial suppression of insulin secretion achieved with a low-dose infusion of somatostatin reduces the clearance rate of endogenously secreted insulin (32).…”
Section: Discussionmentioning
confidence: 99%